Exploring teacher educator knowledge - Lay, Celina Dulude (Advances in research on teaching ;, 2024)
Teacher educator knowledge in curriculum development is situated in a space that is tacit and embodied. It is important to recognize that within the realm of teacher education (as opposed to K-12 classrooms), this knowledge is complex and draws upon nuanced personal practical expertise. When research is situated in self-study, it enables teacher educators to transition from tacit and embodied understanding to explicit knowledge that can be communicated. Considering these aspects, Celina Dulude Lay explores the use of narrative vignettes as data; the vignettes demonstrate knowledge of content, the fixed and fluid elements of course design attending to milieu, pedagogical intent, preservice teacher knowledge and belief, the value and fragility of relationships, and theory. Exploring Teacher Educator Knowledge lays the foundation for teacher educators, promoting strategies and methodology to support and foster practical and theoretical knowledge.